Mortalidade por tuberculose associada à infecção por HIV/AIDS na cidade de Fortaleza - Gadelha, Raimunda Rosilene Magalhães (2012)
One of the most critical problems related to HIV / tuberculosis (TB) coinfection is the associate mortality. HIV infection has contributed to the increase in the number of TB cases and has even been responsible for the increased mortality among coinfected patients. Fortaleza, located in Northeastern Brazil, is one of the urban centers with the highest incidence of TB in the country. This research evaluates clinical, epidemiological characteristics and risk factors related to mortality from TB in patients coinfected with HIV / AIDS, aged 12, residents in the city of Fortaleza. It was performed a retrospective, descriptive and case-control study. Database were reviewed in 262 charts of patients with TB active treated at four clinics reference to HIV / AIDS in Fortaleza between the years 2004-2008. The profile of these patients is characterized by young adults, low education, and common habits of alcoholism (41.98%), smoking (33.59%) and illicit drug use (26.72%). The majority (65.65%) showed the first time TB. In the clinical presentation, pulmonary TB was observed in 50% of cases. The majority (62.98%) underwent hospitalization during treatment of TB. The use of anti retrovirias was more frequent in patients who progressed to cure or end of treatment (88.0%). The mortality rate was 11.45% and the coefficient of abandonment of 16.03%. In univariate analysis, the individual separated / widowed have 3.7 times greater risk of death from TB, and 100% of new cases died. X-ray examination showed a changed ratio of 31% of deaths. The diagnosis of HIV due to TB was a protective factor against death (OR = 0.25). Mean viral load before TB was higher in the case group (p = 0.04). The start of ART was another protective factor for death (OR = 0.11). In the final model of logistic regression, we found that the individual who had no response to treatment is 9.9 (p = <0.01) times more likely to lead to death and the individual who has not started antiretroviral 10.1 (p = <0.01) more times. These results are important for planning and development of actions for the control of TB in patients with HIV infection / AIDS in Fortaleza.